2004
DOI: 10.1162/15353500200403193
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Dynamics of Gene Expression in the Living Mouse

Abstract: Reporter genes can monitor the status and activity of recombinant genomes in a diverse array of organisms, from bacteria and yeast to plants and animals. We have combined luciferase reporter genes with a conditional gene expression system based on regulatory elements from the lac operon of Escherichia coli to visualize the dynamics of gene expression in realtime in the living mouse. Using this technology, we have determined the rate of gene induction and repression, the level of target gene activity in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In a subsequent study, similar control of gene expression during embryogenesis was demonstrated in vivo for a luciferase reporter gene under the control of the ubiquitous Huntingtin promoter with introduced LacO sites (Huntingtin Lac O ‐luciferase) (Ryan & Scrable, 2004). In this study it was shown that luciferase activity could be regulated in live offspring in utero by the addition of IPTG to the drinking water of the pregnant dam (Ryan & Scrable, 2004).…”
mentioning
confidence: 76%
“…In a subsequent study, similar control of gene expression during embryogenesis was demonstrated in vivo for a luciferase reporter gene under the control of the ubiquitous Huntingtin promoter with introduced LacO sites (Huntingtin Lac O ‐luciferase) (Ryan & Scrable, 2004). In this study it was shown that luciferase activity could be regulated in live offspring in utero by the addition of IPTG to the drinking water of the pregnant dam (Ryan & Scrable, 2004).…”
mentioning
confidence: 76%
“…Orientation was verified by analytical restriction enzyme digest. The generation of the human pHDluc reporter construct has been described previously (Ryan and Scrable, 2004).…”
Section: Generation Of Huntingtin Reporter Constructsmentioning
confidence: 99%
“…For instance, a tetO and lacO doubly modified gene could be controlled in two different tissues using specific combinations of lacI and (r)tTA or (r)tTS under the control of two tissuespecific promoters; addition or removal of doxycycline and IPTG would then determine the specific activation status in each of the tissues in a reversible fashion. A transgenic model using this system and a luciferase reporter that allows the evaluation of the dynamics of gene expression in the living animal has recently been described (72).…”
Section: The Lac Systemmentioning
confidence: 99%